Analisis Hasil Belajar Matematika Siswa Kelas VIII SMP Pada Pokok Bahasan Statistika Dikaitkan Dengan Intelligence Quotient (IQ) - Hisyam Ihsan; Rusli; Selvi Rahmatia (Issues in Mathematics Education (IMED), 2019)
This study aims to determine the relationship between mathematics learning outcomes and student intelligence levels. The subjects of this study were VIII grade students in one of the junior high schools in Makassar. Taking the subject by giving a test to students of class VIII 5 then from the results, selected 3 subjects based on existing categories. The instrument used was a learning achievement test containing 5 questions and an IQ test containing 38 questions. The results of the research showed that the VIII grade students had a significant influence on student learning outcomes and Intelligence Quotient so it obtains diverse results. There is also one student who has a high IQ but low learning outcomes.